2009
DOI: 10.1002/adsc.200800637
|View full text |Cite
|
Sign up to set email alerts
|

Metathesis in Pure Water Mediated by Supramolecular Additives

Abstract: Supramolecular, water-soluble additives based on calix[n]arenes exhibit a beneficial influence on the ring-closing and cross metathesis of non-polar substrates in pure aqueous medium using standard Grubbs-II and Hoveyda-II catalysts. The catalytic activity observed in water is virtually the same as that in pure methanol. Quantitative yields of metathesis product can be achieved under mild aerobic conditions in/on water by (micro)solubilization of both the catalyst and starting materials by the macrocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 46 publications
0
25
0
1
Order By: Relevance
“…[38] Furthermore, di(methoxy)imidazolium-based salts are used for enhancing reactions in water. [43] As experimental method, we use ARXPS for probing the surface layer of the IL samples. Our Dual Analyzer System for Surface Analysis (DASSA) [44] setup allows for simultaneously recording spectra in a surface sensitive and a bulk sensitive mode, which directly permits to identify surface enrichment or depletion effects of all atoms (apart from hydrogen) being present in the ions.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Furthermore, di(methoxy)imidazolium-based salts are used for enhancing reactions in water. [43] As experimental method, we use ARXPS for probing the surface layer of the IL samples. Our Dual Analyzer System for Surface Analysis (DASSA) [44] setup allows for simultaneously recording spectra in a surface sensitive and a bulk sensitive mode, which directly permits to identify surface enrichment or depletion effects of all atoms (apart from hydrogen) being present in the ions.…”
Section: Introductionmentioning
confidence: 99%
“…In summary,w eh ave shown that 1a and 1b act as as upramolecular containers for a,w-dienes in D 2 Ot og ive extended, coiled, and folded guest complexes as homogeneous solutions.T he cavitand 1b not only dissolves the substrate but also plays arole as template for RCM reactions with aw ater-compatible catalyst. [23] Theh ost-guest interactions bring the reacting ends closer together in aprecyclization conformation that overcomes some internal strains.The yield of seven, eight, and nine-membered cycloalkenes were significantly enhanced even compared with the reaction in homogeneous chloroform phase.T he cavitand buries hydrophobic surfaces and the shape of the space on offer pushes the reactions along congruent pathway,e ven some that are not readily observed in bulk solution.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Metathesis reactions are of high interest because of their tolerance to a variety of functional groups, high yield, and potential chemoselectivity, even of olefins with different substituents, allowing specific cross metathesis reactions. The design of novel, water‐soluble Grubbs catalysts such as the water‐soluble Hoyveda‐Grubbs catalyst (HG2‐S 3 ) and the development of novel protocols to allow the use of GI and GII in emulsion have increased interest in the application of metathesis catalysts under aqueous conditions . The use of ROMP in the preparation of biopolymer networks has high potential for biopolymers that are water soluble and show limited solubility in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The design of novel, water-soluble Grubbs catalysts such as the water-soluble Hoyveda-Grubbs catalyst (HG2-S 3) and the development of novel protocols to allow the use of GI and GII in emulsion have increased interest in the application of metathesis catalysts under aqueous conditions. [13][14][15] The use of ROMP in the preparation of biopolymer networks has high potential for biopolymers that are water soluble and show limited solubility in organic solvents. The orthogonality of the metathesis reaction furthermore allows such crosslinking with high chemoselectivity also in the presence of -OH, -NH 2 , or -COOH groups and is only initiated when a suitable catalyst is added.…”
Section: Introductionmentioning
confidence: 99%